Getting to and away from the egg, an interplay between several sperm transport mechanisms and a complex oviduct physiology - Giojalas, Laura Cecilia (2020)
In mammals, the architecture and physiology of the oviduct are very complex, and one long-lasting intriguing question is how spermatozoa are transported from the sperm reservoir in the isthmus to the oocyte surface. In recent decades, several studies have improved knowledge of the factors affecting oviduct fluid movement and sperm transport. They report sperm-guiding mechanisms that move the spermatozoa towards (rheotaxis, thermotaxis, and chemotaxis) or away from the egg surface (chemorepulsion), but only a few provide evidence of their occurrence in vivo. This gives rise to several questions: how and when do the sperm transport mechanisms operate inside such an active oviduct? why are there so many sperm guidance processes? is one dominant over the others, or do they cooperate to optimise the success of fertilisation? Assuming that sperm guidance evolved alongside oviduct physiology, in this review we propose a theoretical model that integrates oviduct complexity in space and time with the sperm-orienting mechanisms. In addition, since all of the sperm-guidance processes recruit spermatozoa in a better physiological condition than those not selected, they could potentially be incorporated into assisted reproductive technology (ART) to improve fertility treatment and/or to develop innovative contraceptive methods. All these issues are discussed in this review.